DNA-Based Technology for Herpesvirus Detection - Gloria Maini; Giorgia Cianci; Matteo Ferraresi; Valentina Gentili; Daria Bortolotti (DNA)
The detection of viral DNA is considered crucial in both diagnosis and prognosis. Nowadays, molecular diagnostic approaches represent the most promising tools for the clinical detection of viral infections. This review aims to investigate the most used and promising DNA-based technologies for viral detection, focusing on herpesviruses because of their ability to undergo latent and reactivation cycles, persisting lifelong in the host in association with several diseases. Molecular technologies, such as PCR-based assays, enhance sensitivity and specificity in identifying viral DNA from clinical samples such as blood, cerebrospinal fluid and saliva, indicating PCR and its derivatives as the gold standard methods for herpesvirus detection. In conclusion, this review underscores the need for continuous innovation in diagnostic methodologies to address the complexities of herpesvirus identification in different clinical samples.